Sequential, One-Pot Access to Arylated Benzoquinones/Naphthoquinones from Phenols/Naphthols - Jiang, Jia-Heng; Boominathan, Siva Senthil Kumar; Hu, Wan-Ping; Chen, Chung-Yu; Vandavasi, Jaya Kishore; Lin, Ying-Ting; Wang, Jeh-Jeng (European journal of organic chemistry, 2016)
A sequential one‐pot approach towards arylated benzoquinones and naphthoquinones is reported. The reaction proceeds through oxidation of phenols/naphthols followed by CH‐arylation with a catalytic amount of triflic acid. Preliminary cytotoxic studies were carried out with five different cell lines and some of the compounds show promising activity. This one‐pot approach towards arylated benzoquinones and naphthoquinones proceeds through oxidation of phenols/naphthols followed by CH‐arylation. Preliminary cytotoxic studies for some of the compounds showed promising activity.